Probabilistic seismic demand models for circular tunnels subjected to transversal seismic load. (July 2022) - Zhao, Guochen; Gardoni, Paolo; Xu, Longjun; Shu, Fengyuan; Xie, Lili
Highlights: Uncertainties in the earthquake intensity, seismic load, and calculation methods are considered. Three demands moment, thrust, and diametric distortion are considered. Analytical method is used as an integral part of the seismic demand models. Bayesian approach is used to estimate the unknown model parameters. The probability distributions of the seismic demands can be obtained. Abstract: This paper proposes convenient probabilistic models to estimate the seismic demands of circular tunnels to transversal seismic load. The uncertainties in the earthquake intensity, seismic load, and calculation methods are fully considered. Peak ground velocity PGV is selected as an essential earthquake intensity parameter because it is more correlated with the earthquake damage of underground structures, and a probabilistic model of PGV is proposed. Because the seismic response of tunnel linings is highly correlated with the free-field ground deformation, the maximum free field shear strain g max is selected as the seismic load parameter. A probabilistic model of g max is developed based on a series of seismic site response analyses. PGV plays a key role in the estimation of g max . The analytical methods have been proposed to estimate the seismic response of tunnels. However, the results are usually biased, and the underlying uncertainties have not been well studied. To obtained unbiased seismic response estimates and capture the uncertainties in the calculation methods, the probabilistic seismic demand models are constructed by developing correction terms to the analytical method. The maximum moment M max, thrust T max, and diametric distortion Δ d / d max of the tunnel lining are considered. A pseudo-static analysis approach is used to simulate the seismic response of tunnels, and Bayesian updating is used for the model optimization and parameter estimation. The results of this paper can be used in the seismic design and reliability analysis of circular tunnels.